TRANSFORMATIVE DIALOGUE OF PESANTREN THROUGH TASAWUF VALUES IN POST-CONFLICT DERADICALIZATION IN POSO REGENCY - Saude, Saude; Firmansyah, Eka; Hamka, Hamka; Khalil, Abdelmajid Idris Mohammed (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This research examines the mechanism of multi-stakeholder transformative dialogue in transforming pesantren orientation through tasawuf values and its relationship with post-conflict deradicalization. Method: A qualitative case study was conducted at Pondok Pesantren Tahfidzul Qur'an Amanah, Poso, Sulawesi Tengah during 12 months (January-December 2024) through observation, interviews, participant observation, and document analysis with a theoretical framework integrating positive dialogue theory from Bourdieu and 45% (2010) positive impacts. Result: The research findings reveal a comprehensive dialogue model that integrates: (1) ekogrit (recognition ecology) transforming rigid understanding of religious uniformity; (2) restructuring curriculum and pedagogy towards contextual-substantivist approaches rather than textualist-formalist such as low self-esteem, patience, and universal love; (3) implementation of sustainable dialogue with multi-religious communities based on the principle of ukhuwan insaniyyah (universal brotherhood) and sulh (reconciliation). Tasawuf values such as iksan, qana'ah, and dzikir practices strengthen collective identity and spiritual resilience in facing post-conflict trauma. Conclusion: The transformation produces tangible impacts: trust among religious communities increased 78% (2010 to 2024), inter-religious conflicts decreased from 12 cases/year to almost zero since 2016, membership growth in Koperasi Syariah Lintas Agama reached 457%, and the deradicalization model based on tasawuf values is replicable for 128,000 pesantren in Indonesia, contributing significantly to SDG 16 regarding peace, justice, and strong institutions.